Secondary School Students' Test Anxiety as a Correlate of Their Academic Achievement in Biology in Anambra State, Nigeria - Nwuba, Izunna Shedrack; Obikezie, Maxwell Chukwunazo; Chinwe, Joy Chidinma; Agbo, Loveth Chinaza; Mbaegbu, Chioma Stephanie; Anyigor, Chisom Precious (International Journal of Education, 2024)
The growing need to improve students’ performance in biology in external examinations has driven science educators on the quest for factors, both personal and environmental, that could be influenced to this effect. Considering this, the study investigated the relationship between secondary school students’ test anxiety and their academic achievement in biology. Two research questions and three null hypotheses, tested at 0.05 alpha levels, guided the study. A correlational survey research design was adopted. The population comprised the 20,703 Senior Secondary Year one (SS1) students, in the 262 government owned secondary schools, in Anambra State. Taro Yamane’s formula was employed to obtain the sample size of 392 SS1 students while proportionate stratified random sampling technique was used to randomly draw the students used in the study. For data collection, two instruments were used: The Biology Test Anxiety Scale (BTAS), which was validated by three experts and with a reliability coefficient of 0.78 established using Cronbach alpha, and the Biology Students' Score Proforma (BSSP). Data collected were analyzed using Pearson product moment coefficient (r) to answer the research questions while the hypotheses were tested at 0.05 alpha levels using simple linear regression. The findings of the study revealed that, statistically, students test anxiety negatively correlates with their academic achievement in biology, irrespective of gender. This by implication simply means that as students’ test anxiety increases, their academic achievement decreases. Based on the findings, the study recommended among others that teachers should allocate adequate time, adopt innovative strategies and organize practical classes during biology classes as these will encourage active participation, boost students’ morale and, in the long run, reduce their test anxiety in biology.